2023
DOI: 10.1177/10892532231184781
|View full text |Cite
|
Sign up to set email alerts
|

Left-Sided Double-Lumen Tube vs EZ-Blocker for One-Lung Ventilation in Thoracic Surgery: A Systematic Review and Meta-Analysis

Abstract: Background. The EZ-Blocker is the newest generation of bronchial blocker and offers a potential alternative to left-sided double lumen tubes for lung isolation and one-lung ventilation during thoracic surgery. Methods. Databases were searched for randomized controlled trials comparing left-sided double lumen tube to the EZ-Blocker for one-lung ventilation during thoracic surgery. The time for placement, incidence of intraoperative displacement, and surgeons’ rating of lung collapse quality were designated as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Our second Original Research article is a demonstration of this, evaluating the existing literature comparing the Rüsch ® EZ-Blocker™ to the more traditional left-sided double lumen tube (L-DLT) for lung isolation in thoracic surgery. 7 In a systematic review and meta-analysis spanning 6 studies and 495 patients, Kumar and colleagues found that the L-DLT tube was faster to place by over a minute (mean difference À61.24 seconds; 95% CI À102.48 to À20.00; P = .004), a finding supported by previous work 8 demonstrating faster placement of L-DLTs as compared to a pooled group of all bronchial blockers. This analysis also found that L-DLTs were much less likely to be displaced during lung isolation with an odds ratio of .56 (95% CI .34 to .91; P = .02), though these advantages came at the cost of a greater degree of postextubation sore throat.…”
mentioning
confidence: 77%
“…Our second Original Research article is a demonstration of this, evaluating the existing literature comparing the Rüsch ® EZ-Blocker™ to the more traditional left-sided double lumen tube (L-DLT) for lung isolation in thoracic surgery. 7 In a systematic review and meta-analysis spanning 6 studies and 495 patients, Kumar and colleagues found that the L-DLT tube was faster to place by over a minute (mean difference À61.24 seconds; 95% CI À102.48 to À20.00; P = .004), a finding supported by previous work 8 demonstrating faster placement of L-DLTs as compared to a pooled group of all bronchial blockers. This analysis also found that L-DLTs were much less likely to be displaced during lung isolation with an odds ratio of .56 (95% CI .34 to .91; P = .02), though these advantages came at the cost of a greater degree of postextubation sore throat.…”
mentioning
confidence: 77%
“…Double-lumen tubes (DLT) and bronchial blockers (BB) are the most commonly used airway tools in thoracic surgery 1 . They allow isolation of the operative lung from the non-operative lung, which prevents contamination of the non-operative lung by pollutants, such as blood and sputum 2 . However, in thoracoscopic lobectomy, these two options only protect the non-operative lung from contamination and do not protect the non-operative lobe(s) of the operative lung.…”
Section: Introductionmentioning
confidence: 99%